A Novel Risk Stratification System for Thyroid Nodules With Indeterminate Cytology—A Pilot Cohort Study - Gomes-Lima, Cristiane J.; Auh, Sungyoung; Thakur, Shilpa; Zemskova, Marina; Cochran, Craig; Merkel, Roxanne; Filie, Armando C.; Raffeld, Mark; Patel, Snehal B.; Xi, Liqiang; Wartofsky, Leonard; Burman, Kenneth D.; et al. (Frontiers in Endocrinology, 2020)
Background: Thyroid ultrasound (US), fine needle aspiration biopsy (FNAB) and molecular testing have been widely used to stratify the risk of malignancy in thyroid nodules. The goal of this study was to investigate a novel diagnostic approach for cytologically indeterminate thyroid nodules (ITN) based upon a combination of US features and genetic alterations. Methods: We performed a pilot cohort study of patients with ITN (Bethesda III/IV), who underwent surgical treatment. Based on standardized sonographic patterns established by the American Thyroid Association (ATA), each ITN received an US score (XUS), ranging between 0 to 0.9 according to its risk of thyroid cancer (TC). DNA and RNA were extracted from pathologic material, available for all patients, and subjected to Oncomine™ Comprehensive Assay v2 (OCAv2) next-generation sequencing. Each genetic alteration was annotated based on its strength of association with TC and its sum served as the genomic classifier score (X). The total risk score (TRS) was the sum of XUS and XGC. ROC curves were generated to assess the diagnostic accuracy of XUS, XGC and TRS. Results: The study cohort consisted of 50 patients (39 females and 11 males), aged 47.5±14.8 years. Three patients were excluded due to molecular testing failure. Among the remaining 47 patients, 28 (59.6%) were diagnosed with TC. BRAFV600E was the most common mutation in papillary TC, PAX8-PPARG fusion was present in NIFTP, pathogenic variants of SLX4, ATM and NRAS were found in Hürthle cell TC and RET mutations in medullary TC. The diagnostic accuracy of XGC and TRS was significantly higher compared with XUS (88% vs 62.5%, p<0.001; 85.2% vs 62.5%, p<0.001, respectively). However, this increased accuracy was due to significantly better sensitivity (80.7% vs 34.6%, p<0.001; 84.6% vs 34.6%, p<0.001, respectively) without improved specificity (94.7% vs 90%, p=0.55; 85.7% vs 90%, p=0.63, respectively). Conclusion: Molecular testing might not be necessary in ITN with high-risk US pattern (XUS=0.9), as specificity of TC diagnosis based on Xus alone is sufficient and not improved with molecular testing. OCAv2 is useful in guiding the management of ITN with low-to-intermediate risk US features (XUS<0.9), as it increases the accuracy of TC diagnosis.